Potensi Konflik Perkawinan Lintas Budaya Perempuan Indonesia dan Laki-Laki Bule - Benazir Bona Pratamawaty (Kafa`ah: Journal of Gender Studies, 2017)
The intercultural marriages are frequently encountered by many problems and conflicts. One of the causes is the cultural background differences. This kind of marriage occurs between Indonesian women and the foreigner, the mixing between different cultural background, western and eastern culture. This research was aimed at identifying and recognizing the conflict that caused by the intercultural marriages of the Indonesian women and the caucasians. This research is one part of a broader scope of research using a phenomenological approach,in terms of particular symbolic interaction and social construction theory of reality. Methods of data collection include in-depth interviews and observations of seven Indonesian women who married caucasian and domiciled in Jakarta. The results show some dominant conflict-causing differences in cross-cultural marriages between Indonesian women and male caucasians. The differences include language – context differences, communication style, perceptions on family concepts, and perceptions about privacy. In the end, cross-cultural marriage couples find a pattern of settlement in responding the cultural differences they find in everyday life. Over time, sharing the differences that exist together, the Indonesian .Finally, women and foreign husbands reach the a point where they start sharing the same values and worldviews.